Vertical contact tightness of occlusion comparison between orofacial myalgia patients and asymptomatic controls: a pilot study. Issue 12 (December 2018) - Qi, Kun; Xu, Yi-Fei; Guo, Shao-Xiong; Xiong, Wei; Wang, Mei-Qing
Objective: The association between occlusal contact and orofacial pain remains unclear. The aim of this study was to detect occlusal contact tightness by using a new method and to compare differences between patients and asymptomatic controls. Methods: Fifteen female patients with orofacial myalgia and fifteen age- and sex-matched asymptomatic controls were enrolled. Occlusal contacts were recorded by making bite imprints. The numbers, sizes, and distributions of the contacts were detected by making photos of bite imprints after biting. The Mann-Whitney U test and ANOVA were used for statistical analysis. Results: In myalgia patients, impact contacts at the molar regions were more frequent, larger in number and area size, and were distributed more on guiding cusps, compared with impact contacts in asymptomatic controls. Conclusion: Our new method revealed more prevalent and more severe impact contacts in orofacial myalgia patients, compared with asymptomatic controls.